Hydrofluoric acid concentration, time and use of phosphoric acid on the bond strength of feldspathic ceramics - Moura, Dayanne Monielle Duarte; de Araújo, Arthur Magno Medeiros; de Souza, Karina Barbosa; Veríssimo, Aretha Heitor; Tribst, João Paulo Mendes [UNESP]; de Assunção e Souza, Rodrigo Othávio (FapUNIFESP (SciELO), 2020)
The objective of this study was to evaluate the influence of hydrofluoric acid (HF) concentration, etching time, and application of phosphoric acid (PA) followed by neutralization with sodium bicarbonate on the bond strength between a feldspar ceramic and resin cement. Thus, 80 blocks (10 x 12 x 2 mm) of glass ceramic (VM-Vita Mark II-Vita Zahnfabrik) were made and randomly assigned to eight groups (n = 10) according to the factors: HF concentration (5 and 10%), etching time (60 and 120 s), and use of phosphoric acid (PA) (with and without). According to the experimental group, 37% PA (Condac, FGM) was applied after HF etching for 60s. Afterwards, samples were immersed in sodium bicarbonate for 1 min then in an ultrasonic bath in distilled water (5 min) for cleaning. After surface bonding treatment, cylinders (O = 2 mm; h = 2 mm) of dual resin cement (AllCem / FGM) were made in the center of each block. The samples were then stored in water (37C) for 90 days and submitted to the shear bond test (50 KgF, 1 mm/min). Failure analysis was performed by stereomicroscope and scanning electron microscopy. Data (MPa) were analyzed with 3-way ANOVA and Tukey's test. Only the factor HF concentration was significant (p = 0.02). Most failures were of cohesive in ceramic (40%) and mixed types (42.5%). The 10% HF resulted in higher shear bond strength value than the 5% HF. Surface cleaning with phosphoric acid followed by sodium bicarbonate and HF time (60 or 120 seconds) did not influence the resin bond strength to feldspar ceramic.
Keywords: Ceramics; Hydrofluoric acid; Shear strength